The impact of Joint Commission International (JCI) standards on employees’ job satisfaction at Mahkota Medical Centre, Melaka / Erni Ismail - Ismail, Erni (Faculty of Business and Management, 2011)
Project paper titled “The Impact of Joint Commission International (JCI) standards On Employees’ Job Satisfaction at Mahkota Medical Centre, Melaka” is conducted as partial requirement to fulfil the requirement as needed by the faculty of Business Management, MARA University of Technology (UITM). The purpose of this study is to identify the most factors that influence job satisfaction among employees in the Mahkota Medical Centre, their level of job satisfaction and the significant relationship between factors influencing their job satisfaction. The researcher chooses to use descriptive research design as method and the researcher use survey in order to collect the data. Data used in this research are primary and so on secondary data such as journal and books. Researcher also use questionnaire to obtain the data in order to get the feedback from Mahkota Medical Centre employees.